“Más ganados que frutos”. La evolución de la tenencia de la tierra en Hatoviejo (Bello), Antioquia, siglos XVII a XVIII (2011)
ABSTRACT: This article is an historical approach to the land tenure evolution in Hatoviejo, (Bello, Antioquia, Colombia) during the 17th and 18th centuries. In this article it is studied the mercy fragmentation process of lands that were given by the city of Antioquia town council to the conqueror Gaspar de Rodas in the 16th century, who later ceded them to his sons. In a brief it is shown how those large properties were subdivided to become several cattle farms and farms where most of the food consumed in the province was produced. From notarial registers it is reconstructed the subsequent fragmentation of those farms until the birth of small and medium properties belonging to mestizo people, native people and mulatto people, and having as a conclusion the analysis of the land tenure structure from this studied period.